Proceedings of the 18th International Seminar on Paste and Thickened Tailings 2015
DOI: 10.36487/acg_rep/1504_12_reid
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a proposed steepened beach

Abstract: Existing topography at an operational lateritic nickel facility is such that if the tailings beach slope could be increased to 1-2% for approximately one year, significant costs related to wall building could be deferred. As additional thickening capacity would require significant capital expenditure, polymer treatment technologies have instead been investigated. As part of the trial process for polymer treatment, the stability of the potential steepened beach was assessed. While beach slopes of the range targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore they provided a useful source to perform additional tests to assess the effects of initial slurry density. The results of some of the testing on one of the gold tailings (1) and the iron ore tailings were previously reported by Reid and Fourie (2014), while further details regarding the lateritic nickel tailings are outlined by Reid and Boshoff (2015). Consolidation tests were undertaken using either a 63 mm diameter oedometer, or a 71 mm diameter slurry consolidometer (Sheeran & Krizek 1971), dependent on availability.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore they provided a useful source to perform additional tests to assess the effects of initial slurry density. The results of some of the testing on one of the gold tailings (1) and the iron ore tailings were previously reported by Reid and Fourie (2014), while further details regarding the lateritic nickel tailings are outlined by Reid and Boshoff (2015). Consolidation tests were undertaken using either a 63 mm diameter oedometer, or a 71 mm diameter slurry consolidometer (Sheeran & Krizek 1971), dependent on availability.…”
Section: Methodsmentioning
confidence: 99%
“… Post-cyclic test comparisons using a DSS device outlined by Reid and Boshoff (2015), Reid et al (2015a), and Reid and Fourie (2017a). Most of this testing did not suggest an increase in post-cyclic strength loss in PT samples.…”
Section: Brittleness And/or Post-cyclic Strength Lossmentioning
confidence: 91%
“…Further, cyclic liquefaction behaviour is affected by a number of material properties such as density, fabric, and deposit age. Three published examples of cyclic testing are available to enable comparison between PT and UT material -testing by Reid and Boshoff (2015) on laterite nickel samples, Reid et al (2015a) on iron ore tailings, and by Reid and Fourie (2017a) as part of their study of PT effects on a low-plasticity synthetic tailings. The results of these three test programs are summarised together in Figure 2.…”
Section: Cyclic Resistancementioning
confidence: 99%
“…Owing to the increased application of forms of PT, studies to characterise the effects PT may have on post-deposition geotechnical behaviour of the treated slurry have been undertaken. Broadly, these studies have indicated the following effects of PT: lower consolidated densities at a given vertical effective stress and higher permeability at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Manzotti et al 2014;Beveridge et al 2015;Gholami & Simms 2015;Reid & Boshoff 2015;Riley et al 2015;Znidarcic et al 2015;Reid & Fourie 2016, 2018aAbdulnabi et al 2022), higher undrained shear strengths at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Beier et al 2013;Manzotti et al 2014;Cooling & Beveridge 2015;Gholami & Simms 2015;Reid & Fourie 2016Abdulnabi et al 2022) and higher CSL elevation (Reid & Fourie 2016), and various contrasting outcomes when examining the effects of PT on brittleness in undrained monotonic or post-cyclic shearing (Beier et al 2013;Gholami & Simms 2015;Reid & Fourie 2017) and drastically different penetrometer responses (Reid and Fourie 2018a), with a summary of recent studies provided by Reid and Fourie (2018b).…”
Section: Introductionmentioning
confidence: 99%